PANDANGAN JOHANN FÜCK TERHADAP AL-QUR’AN: Telaah Filologis-Historis dan Relevansinya bagi Studi Al-Qur’an Kontemporer - Rusdeana Rusbandi (AL ITQAN: Jurnal Studi Al-Qur'an, 2026)
This article examines Johann Wilhelm Fück's view of the Qur'an through a philological-historical framework and evaluates its relevance for contemporary Qur'anic studies. The study focuses on how Fück positioned Arabic, the history of European Arabism, and linguistic evidence as entry points for reading the Qur'anic text. This research employs library research with content analysis of Fück's works and recent scholarship on Qur'anic philology, early manuscripts, hermeneutics, and tafsir studies. The findings show that Fück's contribution lies in his affirmation of Arabic philology as an essential discipline in Qur'anic studies, while his approach must be read critically because it emerged from European Orientalism with epistemological assumptions different from those of the Islamic exegetical tradition. The study also finds that developments in paleography, codicology, digital philology, and Indonesian tafsir studies make it possible to reread Fück's legacy in a more balanced way. The article concludes that Fück's ideas can be used as methodological tools, not as a single authority, to strengthen academic dialogue among philology, history, and ulum al-Qur'an.